INSTITUTIONS IN VILLAGE EMPOWERMENT AS AN EFFORT TO IMPROVE DEVELOPMENT IN BANYUASIN REGENCY - M Defri Adi Shah Putra; Andries Lionardo; Alamsyah; Slamet Widodo; Rudy Chendra (RADJA PUBLIKA, 2026)
Study This aim for study dynamics institutional in empowerment village at a time compile strengthening institutional based development in the Regency Banyuasin. Research use approach qualitative with design studies case study to understand interaction inter-factors, social values and norms, and practice developing institutions​ in the empowerment process village. Data obtained through interview in-depth, observation field, and study documentation to actors strategic at the level village and government area.Results study show that implementation empowerment village Still tend oriented administrative and not yet fully push participation substantive society. Conditions the influenced by limitations capacity source Power human, low involvement society, as well as not yet optimally internalization values public in governance​ village. However Thus, the study also found that existence opportunity strengthening institutional through utilization potential local, support source power and development collaboration multi- actor research This produce draft strengthening institutions that emphasize integration between structure institutional, values public, role actors, and participatory processes in creating public value in the form of improvement welfare society, quality service public, and trust public to government village.